Survival Analysis of Brain Tumor Patients: One Year after Surgery - Tika Dwi Tama; Nada Syifa; Erni Astutik (Preventia : The Indonesian Journal of Public Health, 2025)
Surgery is the most performed procedure to treat brain tumors. However, information about the survival of brain tumor patients after undergoing surgery is still limited in Indonesia. This study aimed to determine 1 year survival in brain tumor patients after undergoing surgical procedures and factors associated with patient survival. A retrospective cohort study was conducted in March until April 2023 with subjects of 46 brain tumor patients who were registered at the Gatot Soebroto Army Hospital and underwent surgical procedures in 2018 until 2022. Data on respondent characteristics (gender and age), clinical conditions (tumor location, stage, and tumor classification), date of surgery, and date of death were obtained from medical records. Kaplan Meier was used to determine the 1 year survival of brain tumor patients after surgery, while Cox Proportional Hazard Regression was used to determine factors associated with its survival. Kaplan Meier analysis showed that 1 year survival in post-operative brain tumor patients reached 80.5 percent. Secondary tumor was known to increase the risk of death in post-operative brain tumor patients (aHR 11.432; 95 percent CI 1.394 until 93.767). There was no significant relationship found between sex, age, tumor location, and tumor stage with brain tumor patients’s survival (p-value more than 0.05). Identification of tumor classification needs to be done correctly and as early as possible so that the patient's prognosis becomes better. The therapeutic approach needs to pay attention to the condition of each patient, especially in cases of secondary brain tumors.